The usage of pedagogical technologies in subjects connected with soil studies. - Is’hakova Shoira; Atabayeva Nargiz Karimova (Genius Publishing Group, 2022)
The history of application of pedagogical technologies in Central Asia and their application in Soil Science, Soil Physics and Soil Chemistry.
Keywords: Soil Science; Soil Physics and Soil Chemistry; Yusuf Khos Hajib,; Husain Vaiz Kashifiy